Validation and quantification of extractable age pigments for determining the age of Antarctic krill (Euphausia superba) - McGaffin, AF; Nicol, S; Patti Virtue; Hirano, Y; Matsuda, T; Uchida, I; Candy, SG; Kawaguchi, S (2011)
Antarctic krill, Euphausia superba, hatched from eggs and maintained for four years, were sampled periodically for age-pigment analysis. Extractable pigments from the eye and eyestalk ganglia were quantified using fluorescence intensity and standardised against protein. Three peak fluorescence intensities were detected at wavelengths of excitation 280 nm, emission 625 nm (pigment 1); excitation 355 nm, emission 510 nm (pigment 2); and excitation 463 nm, emission 620 nm (pigment 3). There was a positive correlation between the quantity of pigments 1 and 3 and the age of Antarctic krill. A model was developed to predict age from pigment 3 and to compare it with other age proxies (carapace length and eyeball diameter). The quantity of pigment 3 was the best predictor of age. The pigment method can discriminate between similar sized krill aged 12 and 36 months. Age pigments provide an improved tool for age estimation in Antarctic krill, particularly if used in conjunction with other demographic information.